Human Disobedience Results in Jealousy and Punishment of God Based on Exodus 20:5 - Bobby Kurnia Putrawan (Sekolah Tinggi Alkitab Penyebaran Injil Majalengka, 2021)
Humans often break their relationship with God by disobeying them. Humans live according to their own will, so this has an impact on the damage to the relationship between man and God. Seeing this, the author investigates man's disobedience to God and its effects based on Exodus 20: 5. The study used in this research is a biblical study using the expository approach. The purpose of this writing is what constitutes human disobedience and its impact on humans. The result is that human disobedience results in punishment for humans. The purpose of this punishment was to improve God's relationship with the Israelites and to become the foundation of the Israelites' life.